IMPLEMENTATION OF NATO STANDARDS FOR PROFESSIONAL FOREIGN LANGUAGE TRAINING OF FUTURE BORDER GUARD OFFICERS - Bloshchynskyi, Ihor; Voitiuk, Olena; Khamaziuk, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Foreign language professional training of future border officers is given considerable attention today, because knowledge of the English language should not only ensure communication between representatives of the law enforcement agencies of different countries, but also ensure their effective and clear interaction, and as a result, ensure the appropriate level of national security. The purpose of the article is to determine the aim, tasks and characteristics of the structure of foreign language professional training of border guard cadets taking into account the integrated professional course of the tactical level of the SBGSU L-1B developed in accordance with NATO standards. M e t h o d s . To achieve the aforementioned purpose, the following scientific methods were used: analysis, comparison, substantiation, generalization, systematization of theoretical and practical material. R e s u l t s . The tactical level of the SBGSU L-1B in accordance with the Model of the "Education throughout the military career" principle implementation provides for the study of the academic discipline "Foreign language for professional direction", which is integrated into the educational-professional program "State Border Security". The study of this academic discipline during the higher education students’ training with the integrated tactical level of the SBGSU L-1B is based on the cadets’ studying military topics, which involves the mastery of military terminology, connected with the everyday activities of military personnel, their duties, tasks, professional environment, etc. This course involves studying the following topics: Personal data, Basic combat training of the US Army, Profession of a serviceman, Military structure, Sports training, Military base, Military equipment, NATO School. C o n c l u s i o n s . Since the approval of the Concept of Transformation of the Military Education System in accordance with NATO standards, mastering the English language is one of the educational foundations for the professional development of the future officers. Mastering the English language for professional purposes provides the basis for the effective professional level improvement by studying foreign academic sources on modern trends in the field of the state’s security and defence, as well as establishes productive cooperation with colleagues from border guard agencies of European and North American countries. Prospects for further research are the development and implementation of the academic discipline "Foreign language for professional purposes (English)" as an educational element of the command course of the tactical level of the SBGSU L-1C, as the next stage of a border guard officer’s professional development.